2019
DOI: 10.3889/oamjms.2019.140
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pharmacist Intervention on Improving the Quality of Life of Patients with Type 2 Diabetes Mellitus

Abstract: AIM: To analyse the characteristics, and analyse the impact of pharmacist intervention on quality of life (QOL) outpatients with type 2 diabetes mellitus (T2DM). METHODS: This six-month analytical cohort study was conducted by assessing the patients’ characteristics and their quality of life by distributing a questionnaire, and the 36-Item short form instrument to the patients with T2DM (n = 45) admitted to the Tertiary hospital in Tebing Tinggi. Patients who had mental disorders, HIV-AIDS, liver disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
1
8
0
3
Order By: Relevance
“…Nineteen studies ( 23,26‐28,31‐33,41,42,44,46‐50 , S2–S4, S10) examined the effectiveness of clinical pharmacy interventions on HRQoL. Clinical pharmacy interventions significantly improved the QoL of people with type 2 diabetes compared to usual care in 13 studies ( 26‐28,31,33,41,44,46‐49 , S2, S10). In the remaining six studies ( 23,32,42,50 , S3, S4), clinical pharmacy interventions did not produce significant reduction in QoL of people compared to usual care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen studies ( 23,26‐28,31‐33,41,42,44,46‐50 , S2–S4, S10) examined the effectiveness of clinical pharmacy interventions on HRQoL. Clinical pharmacy interventions significantly improved the QoL of people with type 2 diabetes compared to usual care in 13 studies ( 26‐28,31,33,41,44,46‐49 , S2, S10). In the remaining six studies ( 23,32,42,50 , S3, S4), clinical pharmacy interventions did not produce significant reduction in QoL of people compared to usual care.…”
Section: Resultsmentioning
confidence: 99%
“…The main types of clinical pharmacy interventions delivered by pharmacists were clinical (34 studies), educational (36 studies), counselling and advice (eight studies), person referral services (three studies), independent prescribing (two studies) and ordering laboratory tests (one study). A greater proportion of studies evaluating interventions that combined clinical and educational components resulted in significantly reduced ( p < 0.05) HbA 1c levels (23 out of 25 studies; 21‐24,26,27,30,31,33‐46 ), HRQoL (nine out of 13 studies; 26,27,31,33,41,44,47‐49 ) and improved cost outcomes (four out of six studies; 4,25,50 , S1) for the intervention groups compared with any other types of interventions. The effectiveness of the types of interventions is described in supporting information ( Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Perubahan gaya hidup menimbulkan masalah kesehatan salah satu dari masalah yang timbul adalah Diabetes Melitus Tipe 2 (2). Diabetes mellitus tipe-2 terjadi ketika tubuh tidak lagi dapat memproduksi insulin yang cukup untuk mengimbangi terganggunya kemampuan untuk memproduksi insulin (3,4).…”
Section: Pendahuluanunclassified
“…When considering patient-related outcome measures, pharmacy interventions have achieved statistically significant improvements in the quality of life for those living with type 2 diabetes, in part, by increasing diabetes knowledge and reducing concerns about diabetes medications 14 41. Although the evidence is limited, community pharmacists have also shown that they are capable of providing a breadth of foot care interventions to people with diabetes, resulting in improved foot outcomes 42…”
Section: Community Pharmacy Interventions In Diabetesmentioning
confidence: 99%